Servi??os de cuidados de longa dura????o para idosos: uma an??lise comparativa entre a realidade do Distrito Federal e a Pol??tica Nacional do Idoso - Ribeiro, Paula Regina de Oliveira (2016)
The ageing population in Distrito Federal has been growing with remarkable features that require long-term care services: low, medium and high complexity. Once this is an observational, exploratory, quantitative and qualitative, bibliographic and documentary study, it aimed to evaluate existing long-term care services in Distrito Federal in the light of the National Policy for the Elderly and pertaing legislation, whether these services meet the elderly population???s socio-demographic distribution, as well the characteristics set for each one. The State Secretariat and the Council of Elderly Rights??? data were analyzed in order to identify: a) number of CRAS and elderly assisted in SCFV; b) number of CREAS, their territorial distribution and the services delivered c) which services provided by law are offered in Distrito Federal; d) number of places available in such services, considering the degree of dependence, income, family ties and gender of the elderly in care; e) services territorial distribution. The results pointed out that only the CCI and ILPI services are developed by both the public and private, with such a poor social cover and an irregular socio-demographic distribution, highlighting the lack of planning. It has also been verified that the lack of social services of medium complexity, such as day centers, care homes and home care workers contributes for the institutional sheltering, putting an even greater burden on this service, as it is pursued like the only option by the elderly and their families.